Thyroid-associated orbitopathy is linked to gastrointestinal autoimmunity. (4th September 2014) - Ponto, K A; Schuppan, D; Zwiener, I; Binder, H; Mirshahi, A; Diana, T; Pitz, S; Pfeiffer, N; Kahaly, G J
Summary: Common autoimmune disorders tend to co-exist in the same subjects and cluster in families. The objective of this study was to determine the prevalence of autoimmune co-morbidity in patients with autoimmune thyroid disease (AITD) with and without thyroid-associated orbitopathy (TAO). This was a cross-sectional study conducted at an academic tertiary referral centre. Of 1310 patients with AITD [ n = 777 or 59% with Graves' disease (GD) and n = 533, 41% with Hashimoto's thyroiditis (HT)] followed at a specialized joint thyroid–eye out-patient clinic, 176 (13·4%) had an adult type of the autoimmune polyglandular syndrome, 129 (9·8%) type 1 diabetes, 111 (8·5%) coeliac disease, 60 (4·6%) type A autoimmune gastritis, 57 (4·4%) vitiligo and 25 (1·9%) Addison's disease. Coeliac disease and autoimmune gastritis were associated positively with GD [odds ratio (OR) = 2·18; P = 0·002 and OR = 6·52; P < 0·001], whereas type 1 diabetes, Addison's disease, autoimmune primary hypogonadism, alopecia areata, rheumatoid arthritis and Sjögren's syndrome were 'protective' for GD and thus linked to HT, OR = 0·49 ( P < 0·001), 0·06 ( P < 0·001), 0·25 ( P < 0·001), 0·50 ( P = 0·090) and 0·32 ( P = 0·003), respectively. Of 610 (46·6%) AITD patients with TAO, 584 (95·7%) and 26 (4·3%) had GD and HT, respectively (P < 0·001). TAO was most prevalent in GD patients with coeliac disease (94%, OR = 1·87, P < 0·001). Multivariate analysis showed high OR for coeliac disease and autoimmune gastritis (3·4 and 4·03, both P < 0·001) pertaining to the association with TAO while type 1 diabetes, Addison's disease and alopecia areata were protective for TAO. In patients with TAO, coeliac disease is the most prevalent co-morbid autoimmune condition and rates are increased compared to GD patients without TAO.